Applicability of linear polyethylenimine supported on nano-silica for the adsorption of CO2 from various sources including dry air1. Issue 65 (16th July 2015) - Zhang, Hang; Goeppert, Alain; Prakash, G. K. Surya; Olah, George
<x xml:space="preserve">Abstract</x> Linear polyethylenimine impregnated on nano-silica as effective and easily regenerable CO2 adsorbents for fast adsorption/desorption cycles.